The economics of obesity - Bolin, Kristian; Cawley, John; Grossman, Michael, 1942- (Emerald, 2006)
Obesity, which has increased in most developed countries in the past few decades, is the result of genetics, environment, and individual choices. Economics is useful for studying the individual choices that lead to obesity, explanations for the recent rise in obesity, the treatment options for obesity, and the costs and consequences of obesity for the individual and society. The papers in this volume, devoted to the economics of obesity, illustrate the wide usefulness of the economic approach. The papers in the first section propose and test economic explanations for food-consumption choices and obesity. In particular, they assess the impact of food quality, access to fast food, food prices, legislation, and other factors on diet, physical activity, and body weight. Treatments for obesity, specifically bariatric surgery and anti-obesity drugs, are studied in the second section of this volume.The third section is devoted to the labor market impacts of obesity; evidence from fifteen countries is presented and evaluated. The fourth and final section calculates the impact of obesity on hospital costs and examines the externalities imposed by obesity through health insurance. Taken together, the papers in this volume advance the frontier of knowledge about the causes, implications, and consequences of obesity, and validate the usefulness of the economic approach for studying obesity in particular and medical conditions more generally. This book studies obesity from an economic perspective. It proposes economic explanation for food consumption choices, treatment of obesity, and treatment of the condition. It's international in scope, providing evidence from 15 countries.
Keywords: Obesity.; elektronické knihy; electronic books